Histomorphological study of uropygial gland of pekin duck (Anas platyrhnchos domesticus) - Baghdad Science Journal (مجلة بغداد للعلوم)
The study included 20 birds of Pekin duck (Anas platyrhnchos domesticus) for study the histological of uropygial gland (10 males + 10 females), the weights were between (1411-1582 gm) for males and (1350-1980 gm) female. Routine Histological Techniques was done and stained by Hematoxylin and Eosin (H&E), Periodic Acidic Schiff (PAS), Masson's trichrome stains. Histological sections of the uropygial gland of Pekin ducks showed that the gland consist of the capsule, parenchyma, isthmus and uropygial papillae. The capsule consist of Dense irregular connective tissue. The mean thickness of capsule around the gland lobes were (56.321?17.206µm) and around the uropygial papillae were (67.208?14.996 µm). The capsule tissues continuous in between the secretory tubules to form trabecular.The parenchyma consists from secretory tubules arranged around the central cavity of gland, the cells that lining the secretory tubules consist of four types the basal cells, intermediate cells, secretory cells and degenerative cells.